(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
This article describes the content and essence of planning and organizing integrated lessons in primary education, the problems that pedagogues may face in the process of integrated education and the ways to overcome them. The pedagogical-psychological aspect of the organization of integrated education in the development of students’ mental processes and its importance at the age stages, as well as the organization of the use of game technologies, are discussed.